The Level of Pro-And Anti-Inflammatory Cytokines in Pregnant Women with a History of Cesarean Section (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The results of a follow-up study of 53 pregnant women at 38-40 weeks gestation who were scheduled for cesarean section are presented. The aim of the study was to compare the levels of pro-(IL-1b, IL-6) and anti-inflammatory (IL-10) cytokines in pregnant women delivered by cesarean section. The content of pro - and anti-inflammatory cytokines (IL-1b, IL-6, IL-10) was determined. in blood plasma and endometrium collected immediately after fetal extraction.